Deformation of terrane boundary shear zone (Lakhna shear zone) between Eastern Ghats Mobile Belt and Bastar Craton in Balangir and Kalahandi Districts, Orissa - BISWAL, TK; JENA, SK; DATTA, S; DAS, R; KHAN, K (GEOLOGICAL SOC INDIA, 2000)
The terrane boundary between Eastern Ghats Mobile Belt and the Bastar Craton in Balangir and Kalahandi Districts of Orissa is distinctly marked by nearly two kilometer wide southeasterly dipping ductile shear zone, designated as the Lakhna shear zone. The shear zone has largely developed in the cotton, but for a narrow width within the Eastern Ghats. It is dominated by quartzofeldspathic mylonites characterised by S-C fabric, asymmetric winged porphyroclasts, quartz ribbons and intragranular faults. These structures have been effectively utilized in deducing the sense of shear and evaluating the amount of strain. The results show thrusting of the Eastern Ghats over the Bastar Craton. The minimum amount of throw along the thrust has been estimated to be around 2.5 to 4.7 km assuming a dominant simple shear deformation.